Building resilience and reversing frailty: a randomised controlled trial of a primary care intervention for older adults. (28th February 2023) - Travers, John; Romero-Ortuno, Roman; Langan, John; MacNamara, Fergal; McCormack, Darren; McDermott, Christopher; McEntire, Jude; McKiernan, Joanne; Lacey, Seán; Doran, Peter; Power, Dermot; Cooney, Marie-Therese
Abstract: Background: There is a need for effective primary care interventions that help older people combat frailty and build resilience. Objective: To study the effectiveness of an optimised exercise and dietary protein intervention. Design: Multicentre, randomised-controlled, parallel-arm trial. Setting: Six primary care practices, Ireland. Methods: Six general practitioners enrolled adults aged 65+ with Clinical Frailty Scale score ≤5 from December 2020 to May 2021. Participants were randomised to intervention or usual care with allocation concealed until enrolment. Intervention comprised a 3-month home-based exercise regime, emphasising strength, and dietary protein guidance (1.2 g/kg/day). Effectiveness was measured by comparing frailty levels, based on the SHARE-Frailty Instrument, on an intention-to-treat basis. Secondary outcomes included bone mass, muscle mass and biological age measured by bioelectrical impedance analysis. Ease of intervention and perceived health benefit were measured on Likert scales. Results: Of the 359 adults screened, 197 were eligible and 168 enrolled; 156 (92.9%) attended follow-up (mean age 77.1; 67.3% women; 79 intervention, 77 control). At baseline, 17.7% of intervention and 16.9% of control participants were frail by SHARE-FI. At follow-up, 6.3 and 18.2% were frail, respectively. The odds ratio of being frail between intervention and control groups post-intervention was 0.23 (95% confidence interval: 0.07–0.72; P  = 0.011), adjusting for age, gender and site. Absolute risk reduction was 11.9% (CI: 0.8%–22.9%). Number needed to treat was 8.4. Grip strength ( P  < 0.001) and bone mass ( P  = 0.040) improved significantly. 66.2% found the intervention easy, 69.0% reported feeling better. Conclusion: A combination of exercises and dietary protein significantly reduced frailty and improved self-reported health.